Biostratigraphy, Paleoecology and Astrochronology of early Miocene planktonic foraminifera from the Mediterranean and the North Atlantic Ocean: new perspectives on the Burdigalian GSSP - FABBRINI, ALESSIO (Università degli Studi di Siena, 2019)
This thesis investigates the early Miocene planktonic foraminifera from two sections Contessa section (Italy) and IODP Site U1406 (Newfoundland, Canada), to contribute to the open question of the Aquitanian/Burdigalian boundary. The Burdigalian stage lacks an official Global Stratotype Section and Point, and its base is provisionally set at 20.43 Ma and approximated by the calcareous nannofossil Helicosphaera ampliaperta FO. Following an integrated biostratigraphic approach, the results obtained from the two sections are reported and discussed in the manuscripts contained in this dissertation. For both sections, a new age model is proposed and their semiquantitative and quantitative analyses are presented for planktonic foraminifera, calcareous nannofossils and magnetostratigraphy. After the recognition of two hiatuses in the second section (Site U1406) other studies were performed, for a paleoecological characterisation of the planktonic foraminifera (with statistical analyses) and then a preliminary cyclostratigraphic study. This final and fourth study will eventually lead to the astronomical tuning of the Site and of the bioevents therein recognised. The successful correlation of the hiatuses to regional megahiatuses allowed us to investigate the early Neogene climate evolution from the perspective of the planktonic foraminifera assemblages. In conclusion, the Contessa section is correlated with other reference sections for the early Miocene. The first correlation was with the Santa Croce di Arcevia Section, which used to be the most complete lower Miocene section in the Mediterranean area (before its closure). The second correlation presented is with the IODP Site U1406 in order to compare the different results obtained from the Mediterranean and the North Atlantic integrated biostratigraphy. A third and final correlation is presented between the two sections here studied and the ODP Hole 926B (in the equatorial Atlantic at Ceara Rise), which is retained a reference section for biostratigraphic and ...